Switching phenomena in magnetic vortex dynamics - Gaididei, Yuri B.; Kravchuk, Volodymyr P.; Mertens, Franz G.; Sheka, Denis D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Amagnetic nanoparticle in a vortex state is a promising candidate for the information storage. One bit of information corresponds to the upward or downward magnetization of the vortex core (vortex polarity). Generic properties of the vortex polarity switching are insensitive of the way how the vortex dynamics was excited: by an ac magnetic field, or by an electrical current. We study theoretically the switching process and describe in detail its mechanism, which involves the creation and annihilation of an intermediate vortex-antivortex pair.